2017
DOI: 10.1038/srep46232
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic traits of Salmonella Montevideo in experimental infections in vivo and in vitro

Abstract: Salmonella serovar Montevideo (SM) is frequently associated with human Salmonella infections and causes gastrointestinal disease, cases are common particularly among individuals who come in close contact with live poultry or poultry meat products. To characterize SM disease in chickens, the pathogenic traits and tissue predilections of the disease were investigated. Dissemination of fluorescent-tagged SM (JOL1575GFP) was monitored after oral and intramuscular mock infections of specific-pathogen-free chickens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This gap in this serovar's epidemiology is probably due to the fact that S. Montevideo is a highly clonal Salmonella serovar, and epidemiological investigations using PFGE, currently the gold standard method, are limited in their ability to differentiate strains implicated in epidemic outbreaks (151). However, a recent study performed by Lalsiamthara and Lee (152) reported that cattle are commonly affected by this serovar and indicated that this serovar is more adapted to chicken than other animals, suggesting that poultry is the primary reservoir. However, interesting information corroborating the findings reported here indicates that although outbreaks in the United States caused by the Montevideo serovar increased in ten years (2002 to 2012) from 728 to 1,203, the prevalence of this bacterium in poultry meat was reduced from 0.25% to 0.1% in this same period, coherent with a negative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in this serovar's epidemiology is probably due to the fact that S. Montevideo is a highly clonal Salmonella serovar, and epidemiological investigations using PFGE, currently the gold standard method, are limited in their ability to differentiate strains implicated in epidemic outbreaks (151). However, a recent study performed by Lalsiamthara and Lee (152) reported that cattle are commonly affected by this serovar and indicated that this serovar is more adapted to chicken than other animals, suggesting that poultry is the primary reservoir. However, interesting information corroborating the findings reported here indicates that although outbreaks in the United States caused by the Montevideo serovar increased in ten years (2002 to 2012) from 728 to 1,203, the prevalence of this bacterium in poultry meat was reduced from 0.25% to 0.1% in this same period, coherent with a negative relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of the myo -inositol metabolic island provides the most compelling evidence for a genetic mechanism underlying clade IV isolates being plant-associated, given that seeds and nuts (common vehicles for Montevideo outbreaks) contain concentrated levels of myo -inositol, which is noted for its role in energy and phosphorus storage in seeds and plants [ 90 ]. Moreover, clade IV members were found to encode virulence factors including the secreted effector AvrA, noted for dampening host immunity [ 60, 91, 92 ], and a Typhimurium-like PipB2 shown to be important in SCV maturation and maintenance ( Table 1 ), as well as a version of SPI-6 showing greater homology with that found in serovar Paratyphi A than Typhimurium ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is a gram-negative bacterium, and it is one of the major pathogens to cause gastrointestinal diseases worldwide [1], [2]. Every year, there are about 20 to 40 million cases of gastroenteritis caused by the infection of Salmonella, and the associated economic loss is more than 2 billion US dollars, which brings serious threat to the world public health [3].…”
Section: Introductionmentioning
confidence: 99%